Origins of language : constraints on hypotheses - Johansson, Sverker, 1961- (Converging evidence in language and communication research, 2005)
"Sverker Johansson has written an unusual book on language origins, with its emphasis on empirical evidence rather than theory-building. This is a book for the student or researcher who prefers solid data and well-supported conclusions, over speculative scenarios. Much that has been written on the origins of language is characterized by hypothesizing largely unconstrained by evidence. But empirical data do exist, and the purpose of this book is to integrate and review the available evidence from all relevant disciplines, not only linguistics but also, e.g., neurology, primatology, paleoanthropology, and evolutionary biology. The evidence is then used to constrain the multitude of scenarios for language origins, demonstrating that many popular hypotheses are untenable."--Jacket